Monovalent Lectin Microvirin Utilizes Hydropathic Recognition of HIV-1 Env for Inhibition of Virus Cell Infection - Bibek Parajuli; Kriti Acharya; Harry Charles Bach; Shiyu Zhang; Cameron F. Abrams; Irwin Chaiken (Viruses, 2025)
Microvirin is a lectin molecule known to have monovalent interaction with glycoprotein gp120. A previously reported high-resolution structural analysis defines the mannobiose-binding cavity of Microvirin. Nonetheless, structure does not directly define the energetics of binding contributions of protein contact residues. To better understand the nature of the MVN-Env glycan interaction, we used mutagenesis to evaluate the residue contributions to the mannobiose binding site of MVN that are important for Env gp120 glycan binding. MVN binding site amino acid residues were individually replaced by alanine, and the resulting purified recombinant MVN variants were examined for gp120 interaction using competition Enzyme-Linked Immunosorbent Assay (ELISA), biosensor surface plasmon resonance, calorimetry, and virus neutralization assays. Our findings highlight the role of both uncharged polar and non-polar residues in forming a hydropathic recognition site for the monovalent glycan engagement of Microvirin, in marked contrast to the charged residues utilized in the two Cyanovirin-N (CVN) glycan-binding sites.